A battery negative electrode material and preparation method thereof, and a zinc ion battery and preparation method thereof

By preparing an artificial interface layer of 1,3,5,9-tetrathiophenylene (TTP) on zinc metal foil of zinc ion battery, the problems of zinc dendrites formation and interface side reactions were solved, significantly extending the cycle life of the battery and improving the Coulomb efficiency.

CN115472839BActive Publication Date: 2025-03-25CHUTIAN NEW ENERGY TECH (CHANGCHUN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211206391.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2025-03-25
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

Due to the uneven internal electric and ionic fields of the aqueous zinc ion battery, the formation of zinc dendrites, severe side reactions and surface corrosion at the interface, resulting in short battery cycle life and low Coulomb efficiency.

Method used

Zinc metal foil with an artificial interface layer was used as the negative electrode material of the battery. The artificial interface layer consisted of 1,3,5,9-tetrathiophenylene (TTP) and a binder, and was prepared by spin coating and vacuum drying treatment.

Benefits of technology

Effectively inhibit the formation of zinc dendrites, extend the cycle life of the battery, and improve the Coulomb efficiency, so that the battery exhibits stable low voltage hysteresis and long cycle stability under high current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115472839B_ABST
    Figure CN115472839B_ABST
Patent Text Reader

Abstract

The invention relates to a battery negative electrode material and a preparation method thereof, and a zinc ion battery and a preparation method thereof, which solve the problems of the existing aqueous zinc ion battery, such as the formation of zinc dendrites due to the internal uneven electric field and ion field, and the serious side reactions and surface corrosion at the interface, which lead to the short battery cycle life and low coulomb efficiency. The battery negative electrode material of the invention uses TTP as the zinc negative electrode artificial interface layer, and the negative electrode material can be used to obtain a dendrite-free aqueous zinc ion battery with a long cycle life. TTP as the artificial interface layer can, on the one hand, block the direct contact between the zinc negative electrode and the electrolyte, inhibit the surface side reactions and hydrogen evolution reaction; on the other hand, it can effectively inhibit the formation of zinc dendrites and induce uniform zinc deposition, thereby extending the battery cycle life, so that the assembled symmetrical battery has a high efficiency of 0.885 mA cm ‑2 The cell cycle was stable for nearly 1000 hours at a polarization voltage of 51 mV at a current density of 1.5 %. Meanwhile, the half-cell coulombic efficiency reached 99.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of zinc ion batteries, and in particular relates to a battery negative electrode material and a preparation method thereof, and a zinc ion battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have ideal properties such as low energy consumption, high specific capacity and specific energy, wide operating temperature range, and long storage life. They can be widely used in portable electronic devices, etc., and have always dominated the application market of portable electronic products and electric vehicles. However, problems such as the disordered growth of lithium dendrites during the cycle, the flammable and non-degradable organic electrolytes, and the insufficient sustainability of lithium resources have attracted increasing attention, posing challenges to the further commercial development of lithium-ion batteries. Therefore, many researchers have turned their attention to the development of aqueous zinc-ion batteries with high energy density, high cost performance, safety, and environmental protection. The battery uses an aqueous electrolyte, and its transmission rate is about two orders of magnitude higher than that of an organic electrolyte, and it has a fairly high safety. It has a capacity of 820mA hg -1 The high theoretical capacity and low redox potential of -0.76V vs. SHE, as well as the advantages of simple preparation process, have broad application prospects in the field of large-scale energy storage devices. However, it still faces many thorny problems, especially in the zinc metal negative electrode, such as zinc dendrite growth, hydrogen evolution reaction, by-product formation and surface corrosion.

[0003] The performance of the zinc negative electrode determines the overall performance of the battery. Therefore, the selection of an artificial interface layer to achieve interface modification of the zinc negative electrode has been recognized as a simple and effective method in recent years. The materials currently used to construct the artificial interface layer mainly include carbon materials with good conductivity, inorganic oxide materials, organic polymer materials, etc. Organic materials are usually more flexible than inorganic materials. In the case of electrode volume expansion during long-term battery charging and discharging, they are less likely to fall off and break. In addition, a variety of functional groups have many zinc deposition active sites, which is very conducive to regulating uniform zinc deposition. Therefore, they are more valuable for research and large-scale application. Summary of the invention

[0004] The present invention aims to solve the technical problems in the prior art that aqueous zinc ion batteries, due to the formation of zinc dendrites and severe side reactions and surface corrosion at the interface, lead to short battery cycle life and low coulombic efficiency. A battery negative electrode material and a preparation method thereof, a zinc ion battery and a preparation method thereof are provided.

[0005] In order to solve the above technical problems, the technical solutions of the present invention are as follows:

[0006] The present invention provides a battery negative electrode material, which is a zinc metal foil with an artificial interface layer; the artificial interface layer includes 1,3,5,9-tetrathienylpyrene (TTP for short) and a binder;

[0007] The structural formula of the 1,3,5,9-tetrathienylpyrene is as follows:

[0008]

[0009] In the above technical solution, preferably, the binder is polyvinylidene fluoride (PVDF for short).

[0010] In the above technical solution, preferably, the mass ratio of the 1,3,5,9-tetrathienylpyrene to the binder is 8:1.

[0011] The present invention provides a method for preparing a negative electrode material for a battery, comprising the following steps:

[0012] The zinc metal foil is polished with sandpaper to remove zinc oxide on its surface, and then the polished zinc metal foil is made into an electrode sheet with a puncher. The electrode sheet is then placed in a coating machine and spin-coated with a mixed solution including 1,3,5,9-tetrathienylpyrene and a binder, and then vacuum dried.

[0013] In the above technical solution, preferably, the spin coating conditions are: rotation speed of 1500 rpm and rotation time of 15 s.

[0014] In the above technical solution, preferably, the vacuum drying treatment is carried out under the following conditions: vacuum drying treatment at a drying temperature of 80° C. for 16 hours.

[0015] The present invention also provides an aqueous zinc ion battery, which is a symmetrical battery, and its battery structure includes a positive electrode shell, a positive electrode material, an electrolyte, a diaphragm, an electrolyte, a negative electrode material, a gasket, a spring sheet and a negative electrode shell;

[0016] The positive electrode material is the same as the negative electrode material, which is a zinc metal foil with an artificial interface layer, and the artificial interface layer includes 1,3,5,9-tetrathienylpyrene and a binder;

[0017] The electrolyte is a ZnSO4 aqueous solution;

[0018] Or it is a half-cell, whose battery structure includes a positive electrode shell, a positive electrode material, an electrolyte, a separator, an electrolyte, a negative electrode material, a gasket, a spring sheet and a negative electrode shell;

[0019] The positive electrode material is Ti foil;

[0020] The negative electrode material is a zinc metal foil with an artificial interface layer, and the artificial interface layer includes 1,3,5,9-tetrathienylpyrene and a binder;

[0021] The electrolyte is a ZnSO4 aqueous solution.

[0022] In the above technical solution, preferably, the positive electrode shell is a stainless steel button battery shell CR2032 model, the gasket and spring sheet are stainless steel sheets, the negative electrode shell is a stainless steel button battery shell CR2032 model, the diaphragm is Whatman GF / F glass fiber filter paper with a diameter of 1.6 cm, and the concentration of the electrolyte is 2 mol·L -1 , the thickness of the Ti foil is 0.02 mm.

[0023] The present invention also provides a method for preparing an aqueous zinc ion battery containing the negative electrode material of the present invention, comprising the following steps:

[0024] 1) Treatment of positive electrode shell, negative electrode shell, gasket and spring sheet:

[0025] The positive electrode shell, the negative electrode shell, the gasket, and the spring sheet were ultrasonically cleaned using deionized water and anhydrous ethanol respectively;

[0026] 2) Preparation and treatment of negative electrode materials:

[0027] The zinc metal foil is polished with sandpaper to remove zinc oxide on the surface, and then the polished zinc metal foil is made into an electrode sheet with a punch, and the electrode sheet is placed in a coating machine, and a mixed solution including 1,3,5,9-tetrathienylpyrene and a binder is spin-coated, and then vacuum drying is performed;

[0028] 3) Assembly of symmetrical batteries:

[0029] Put the spring sheet, gasket, and negative electrode sheet in the negative electrode shell respectively, drip the electrolyte, put the diaphragm, and then drip the electrolyte to make the diaphragm completely soaked, put the positive electrode sheet in full alignment with the negative electrode sheet, then buckle the positive electrode shell, put it in a plastic ziplock bag and transfer it to the hydraulic battery packaging machine for packaging;

[0030] Or 4) Assembly of half-cell:

[0031] Put the spring sheet, gasket and negative electrode sheet into the negative electrode shell respectively, drip the electrolyte, put in the diaphragm, and then drip the electrolyte to make the diaphragm completely soaked, put the positive electrode sheet Ti foil in full alignment with the negative electrode sheet, then buckle the positive electrode shell, put it into a plastic ziplock bag and transfer it to the hydraulic battery packaging machine for packaging.

[0032] In the above technical solution, preferably, the mixed solution comprising 1,3,5,9-tetrathienylpyrene and a binder in step 2) is specifically a solution in which the solute is TTP and the binder is PVDF, and the solvent is N-methylpyrrolidone (NMP).

[0033] The beneficial effects of the present invention are:

[0034] The battery negative electrode material provided by the present invention uses an organic material of 1,3,5,9-tetrathienylpyrene as an artificial interface layer of a zinc negative electrode. The negative electrode material can obtain a dendrite-free aqueous zinc ion battery with a long cycle life. TTP as an artificial interface layer can block direct contact between the zinc negative electrode and the electrolyte, inhibit surface side reactions and hydrogen evolution reactions (see Figure 1 ); on the other hand, it can effectively inhibit the formation of zinc dendrites and induce uniform zinc deposition, thereby extending the cycle life of the battery, making the assembled symmetrical battery at 0.885 mA cm -2 The cell cycle was stable for nearly 1000 hours at a polarization voltage of 51 mV at a current density of 1.5 %. Meanwhile, the half-cell coulombic efficiency reached 99.5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0036] Figure 1 It is a schematic diagram of suppressing surface dendrite growth and side reactions in an aqueous zinc ion battery using TTP as an artificial negative electrode interface layer of the present invention.

[0037] Figure 2 The aqueous zinc ion symmetric battery prepared by the present invention and the zinc foil with TTP as the artificial interface layer as electrodes are respectively used as electrodes at 0.885 mA·cm -2 Long cycle polarization voltage curve at current density of .

[0038] Figure 3 The aqueous zinc ion symmetric battery prepared by the present invention is a battery having bare zinc and zinc foil with TTP as an artificial interface layer as electrodes, respectively, at 10 mA·cm -2 Cyclic polarization voltage curve at current density of .

[0039] Figure 4 It is a rate polarization voltage curve diagram of an aqueous zinc ion symmetric battery using bare zinc prepared by the present invention and zinc foil with TTP as an artificial interface layer as electrodes at different current densities.

[0040] Figure 5 It is a charge and discharge curve diagram of an aqueous zinc ion half-battery using bare zinc prepared by the present invention and zinc foil with TTP as an artificial interface layer as negative electrodes respectively.

[0041] Figure 6 It is a coulomb efficiency diagram of an aqueous zinc ion half-cell using bare zinc prepared by the present invention and zinc foil with TTP as an artificial interface layer as negative electrodes respectively. DETAILED DESCRIPTION

[0042] The present invention provides a battery negative electrode material, which is a zinc metal foil with an artificial interface layer; the artificial interface layer includes 1,3,5,9-tetrathienylpyrene (TTP for short) and a binder;

[0043] The structural formula of the 1,3,5,9-tetrathienylpyrene is as follows. The preparation method is described in Organic Letters, 2013.15(6): p.1318-1321.

[0044]

[0045] The tert-butyl group is connected at position 7 in the structural formula.

[0046] Preferably, the binder is polyvinylidene fluoride (PVDF for short).

[0047] Preferably, the mass ratio of the 1,3,5,9-tetrathienylpyrene to the binder is 8:1.

[0048] The present invention also provides a method for preparing a negative electrode material for a battery, comprising the following steps:

[0049] The zinc metal foil is polished with sandpaper to remove zinc oxide on its surface, and then the polished zinc metal foil is made into an electrode sheet with a puncher. The electrode sheet is then placed in a coating machine and spin-coated with a mixed solution including 1,3,5,9-tetrathienylpyrene and a binder, and then vacuum dried.

[0050] Preferably, the spin coating conditions are: a rotation speed of 1500 rpm and a rotation time of 15 s; and the vacuum drying conditions are: a vacuum drying treatment at a drying temperature of 80° C. for 16 h.

[0051] The present invention also provides an aqueous zinc ion battery, which is a symmetrical battery, and its battery structure includes a positive electrode shell, a positive electrode material, an electrolyte, a diaphragm, an electrolyte, a negative electrode material, a gasket, a spring sheet and a negative electrode shell;

[0052] The positive electrode material is the same as the negative electrode material, which is a zinc metal foil with an artificial interface layer, and the artificial interface layer includes 1,3,5,9-tetrathienylpyrene and a binder;

[0053] The electrolyte is a ZnSO4 aqueous solution;

[0054] Or it is a half-cell, whose battery structure includes a positive electrode shell, a positive electrode material, an electrolyte, a separator, an electrolyte, a negative electrode material, a gasket, a spring sheet and a negative electrode shell;

[0055] The positive electrode material is Ti foil;

[0056] The negative electrode material is a zinc metal foil with an artificial interface layer, and the artificial interface layer includes 1,3,5,9-tetrathienylpyrene and a binder;

[0057] The electrolyte is a ZnSO4 aqueous solution.

[0058] Preferably, the positive electrode shell is a stainless steel button battery shell CR2032 model, the gasket and spring sheet are stainless steel sheets, the negative electrode shell is a stainless steel button battery shell CR2032 model, the diaphragm is Whatman GF / F glass fiber filter paper with a diameter of 1.6 cm, and the concentration of the electrolyte is 2 mol·L -1 , the thickness of the Ti foil is 0.02 mm.

[0059] The present invention also provides a method for preparing an aqueous zinc ion battery, comprising the following steps:

[0060] 1) Treatment of positive electrode shell, negative electrode shell, gasket and spring sheet:

[0061] The positive electrode shell, the negative electrode shell, the gasket, and the spring sheet were ultrasonically cleaned using deionized water and anhydrous ethanol respectively;

[0062] 2) Preparation and processing of negative electrode sheets:

[0063] The zinc metal foil is polished with sandpaper to remove zinc oxide on the surface, and then the polished zinc metal foil is made into an electrode sheet with a punch, and the electrode sheet is placed in a coating machine, and a mixed solution including 1,3,5,9-tetrathienylpyrene and a binder is spin-coated, and then vacuum drying is performed;

[0064] 3) Assembly of symmetrical batteries:

[0065] Put the spring sheet, gasket, and negative electrode sheet in the negative electrode shell respectively, drip the electrolyte, put the diaphragm, and then drip the electrolyte to make the diaphragm completely soaked, put the positive electrode sheet in full alignment with the negative electrode sheet, then buckle the positive electrode shell, put it in a plastic ziplock bag and transfer it to the hydraulic battery packaging machine for packaging;

[0066] Or 4) Assembly of half-cell:

[0067] Except that the positive electrode is replaced with Ti foil, the rest of the operations are the same as step 3, as follows:

[0068] Put the spring sheet, gasket and negative electrode sheet into the negative electrode shell respectively, drip the electrolyte, put in the diaphragm, and then drip the electrolyte to make the diaphragm completely soaked, put the positive electrode sheet Ti foil in full alignment with the negative electrode sheet, then buckle the positive electrode shell, put it into a plastic ziplock bag and transfer it to the hydraulic battery packaging machine for packaging.

[0069] Preferably, a specific implementation of the method for preparing the aqueous zinc ion battery is:

[0070] 1) Treatment of positive electrode shell, negative electrode shell, gasket and spring sheet:

[0071] The positive electrode shell, negative electrode shell, gasket, and spring sheet were ultrasonically cleaned with deionized water and anhydrous ethanol for 3-5 times respectively, and wiped one by one with alcohol cotton and dried;

[0072] 2) Preparation and processing of negative electrode sheets:

[0073] The zinc foil was polished with sandpaper to remove zinc oxide on its surface, and then the polished zinc foil was punched into an electrode sheet with a diameter of 1 cm. The electrode sheet was placed in a coating machine and spin-coated with a mixed solution of 1,3,5,9-tetrathienylpyrene and a binder at a rotation speed of 1500 rpm for 15 seconds, and then vacuum dried at a drying temperature of 80°C for 16 hours.

[0074] The preparation process of the mixed solution including 1,3,5,9-tetrathienylpyrene and a binder is as follows:

[0075] In a dry environment, 4 mg of TTP and 0.5 mg of PVDF were dissolved in 1 mL of NMP and stirred at room temperature for 12 h.

[0076] 3) Assembly of symmetrical batteries:

[0077] Put the spring sheet, gasket, and negative electrode sheet in the negative electrode shell respectively, drop 70μL of ZnSO4 aqueous solution, put in the GF / F separator, and then drop 70μL of ZnSO4 aqueous solution to make the separator completely soaked. Put the positive electrode sheet in full alignment with the negative electrode sheet, then buckle the positive electrode shell, put it in a plastic ziplock bag and transfer it to the hydraulic battery packaging machine. -2 The battery is packaged under pressure and the battery is kept horizontal before packaging.

[0078] The ZnSO4 aqueous solution preparation process is as follows:

[0079] Take 0.2 mol of ZnSO4 powder and 30 mL of deionized water in a beaker, stir with a glass rod until it is completely dissolved, and then use the glass rod to drain the solution into a 100 mL volumetric flask. Rinse the beaker and glass rod with deionized water several times and transfer them to the volumetric flask. Use a dropper to add deionized water to the scale line of the volumetric flask. Finally, add the prepared 2 mol·L -1 The ZnSO4 aqueous solution is transferred to a container and stored for later use.

[0080] 4) Assembly of half-cell:

[0081] Except that the positive electrode sheet is replaced with a Ti foil with a thickness of 0.02 mm, the rest of the operations are the same as step 3).

[0082] It is further preferred that

[0083] In order to have a deeper understanding of the present invention, the technical solution is clearly and completely described below in conjunction with the embodiments. However, the embodiments of the present invention are only for explaining the present invention rather than limiting the present invention. All other implementation cases obtained by those skilled in the art without making any creative work are within the scope of protection of the present invention.

[0084] The raw materials used in the following examples are all commercially available products.

[0085] Example 1

[0086] The positive electrode shell, gasket, spring sheet and negative electrode shell were ultrasonically cleaned three times with deionized water, each time for 20 minutes, and then the above steps were repeated with anhydrous ethanol, followed by wiping them one by one with alcohol cotton and drying them in a vacuum oven at 80°C. Prepare ZnSO4 aqueous solution, take 0.2mol ZnSO4 powder and 30mL deionized water in a beaker, stir with a glass rod until all dissolved, and then drain the solution into a 100mL volumetric flask with a glass rod, rinse the beaker and glass rod with deionized water several times and transfer them to the volumetric flask, and then use a dropper to add deionized water to the scale line of the volumetric flask, and finally add the prepared 2mol·L -1 The ZnSO4 aqueous solution is stored for later use. Use fine sandpaper to polish the zinc foil, keep the surface as flat as possible, wipe it with alcohol cotton and dry it, then use a hole punch to cut the zinc foil into discs with a diameter of 1 cm for later use, named Zn foil. Prepare TTP solution in a dry environment, dissolve 4 mg of TTP and 0.5 mg of PVDF in 1 mL of NMP, and stir magnetically at room temperature for 12 hours. Use a glue spreader to spin coat the TTP solution on the zinc sheet at a speed of 1500 rpm and a rotation time of 15 seconds. After the spin coating is completed, put it in a vacuum oven and dry it at 80°C for 16 hours for later use, named TTP-Zn foil. Assemble the symmetrical battery part: put the spring sheet, gasket, and negative electrode sheet (TTP-Zn foil) in the negative electrode shell respectively, drop 70μL of ZnSO4 aqueous solution, put in the GF / F separator, and then drop 70μL of ZnSO4 aqueous solution to make the separator completely soaked, put the positive electrode sheet (TTP-Zn foil) in full alignment with the negative electrode sheet, then buckle the positive electrode shell, put it in a plastic self-sealing bag and transfer it to the battery packaging machine, and press it at 50kg cm -2The battery is packaged under pressure of , and it is noted that the battery is always kept horizontal before packaging. Assembling the half-cell part: except that the positive electrode sheet is replaced with a 0.02 mm thick Ti foil, the remaining steps are the same as the symmetrical battery. The positive electrode shell is a stainless steel button battery shell CR2032 model, the gasket and spring sheet are stainless steel sheets, the negative electrode shell is a stainless steel button battery shell CR2032 model, and the diaphragm is Whatman GF / F glass fiber filter paper with a diameter of 1.6 cm.

[0087] Comparison example

[0088] The difference from Example 1 is that in the symmetrical battery, the control example uses Zn foil as the positive and negative electrodes, and in the half-battery, the Zn foil is used as the negative electrode. The rest of the preparation method is the same as that of Example 1.

[0089] Figure 2 The long cycle polarization voltage curve of the aqueous zinc ion symmetric battery with bare zinc and zinc foil with TTP as artificial interface layer as electrodes is shown in the figure. -2 The improved symmetric battery showed a low voltage hysteresis of about 51 mV and an ultra-long cycle stability of nearly 1000 h at a current density of 1.5 200 mAh, while the unmodified bare zinc symmetric battery had a short circuit phenomenon with a sudden increase in polarization voltage after only 170 h of cycling. This may be because the TTP artificial interface layer hindered the direct contact between zinc metal and electrolyte, inhibited the interface side reaction and hydrogen evolution reaction, and at the same time could adjust the ion distribution, so that zinc was uniformly deposited on the electrode, inhibiting the growth of zinc dendrites (see Figure 1 ).

[0090] Figure 3 The aqueous zinc ion symmetric battery prepared by the present invention is a battery having bare zinc and zinc foil with TTP as an artificial interface layer as electrodes, respectively, at 10 mA·cm -2 The cyclic polarization voltage curve at a current density of 10 mA cm -2 The battery exhibited stable low-voltage hysteresis at a current density of , while the unimproved bare zinc symmetric battery experienced a short circuit phenomenon with a sudden increase in polarization voltage, indicating that the TTP artificial interface layer also improved the battery's current density tolerance.

[0091] Figure 4 The figure is a rate polarization voltage curve of a water-based zinc ion symmetric battery with bare zinc and zinc foil with TTP as an artificial interface layer as electrodes at different current densities. -2 Up to 20mA·cm -2 Continuously charged and discharged at a current density of 2 mAh cm -2The capacity of TTP@Zn remained stable during cycling. When the current density was restored to 1 mA cm -2 When the battery is heated to 40 ℃ and 80 ℃, a lower polarization voltage can be restored, while the bare zinc half-cell without improvement cannot complete the rate test, which indicates that the TTP artificial interface layer can also improve the reversibility of the battery.

[0092] Figure 5 The figure is a charge-discharge curve diagram of an aqueous zinc ion half-cell prepared by the present invention with bare zinc and zinc foil with TTP as an artificial interface layer as negative electrodes, respectively. The figure shows that the voltage hysteresis of the half-cell with the TTP artificial interface layer in the initial state and after 150 cycles is 75.6mV and 50.2mV, respectively, which is much lower than that of the bare zinc half-cell without improvement, which is 90mV and 69.1mV, respectively, indicating that the TTP artificial interface layer makes the zinc insertion and extraction process more stable and can promote the passage of zinc ions.

[0093] Figure 6 The diagram is a coulombic efficiency diagram of aqueous zinc ion half-cells prepared by the present invention with bare zinc and zinc foil with TTP as an artificial interface layer as negative electrodes, respectively. The diagram shows that the half-cell with the TTP artificial interface layer maintains a coulombic efficiency of 99.5% in 120 stable cycles, while the bare zinc half-cell without improvement has obvious fluctuations, which indicates that the TTP artificial interface layer improves the reversibility of the battery, which indirectly reflects that it inhibits the growth and side reactions of zinc dendrites.

[0094] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A battery negative electrode material, characterized in that: It is a zinc metal foil with an artificial interface layer; the artificial interface layer includes 1,3,5,9-tetrathienylpyrene and a binder; The structural formula of the 1,3,5,9-tetrathienylpyrene is as follows:

2. The battery negative electrode material according to claim 1, characterized in that: The binder is polyvinylidene fluoride.

3. The battery negative electrode material according to claim 2, characterized in that: The mass ratio of the 1,3,5,9-tetrathienylpyrene to the binder is 8:

1.

4. A method for preparing a negative electrode material for a battery according to any one of claims 1 to 3, characterized in that: The following steps are involved: The zinc metal foil is polished with sandpaper to remove zinc oxide on its surface, and then the polished zinc metal foil is made into an electrode sheet with a puncher. The electrode sheet is then placed in a coating machine and spin-coated with a mixed solution including 1,3,5,9-tetrathienylpyrene and a binder, and then vacuum dried.

5. The preparation method according to claim 4, characterized in that: The spin coating conditions are: rotation speed of 1500 rpm and rotation time of 15 s.

6. The preparation method according to claim 4, characterized in that: The vacuum drying treatment conditions are: vacuum drying treatment at a drying temperature of 80° C. for 16 hours.

7. An aqueous zinc ion battery containing the battery negative electrode material according to any one of claims 1 to 3, characterized in that: It is a symmetrical battery, and its battery structure includes a positive electrode shell, a positive electrode material, an electrolyte, a diaphragm, an electrolyte, a negative electrode material, a gasket, a spring sheet and a negative electrode shell; The positive electrode material is the same as the negative electrode material, which is a zinc metal foil with an artificial interface layer, and the artificial interface layer includes 1,3,5,9-tetrathienylpyrene and a binder; The electrolyte is a ZnSO4 aqueous solution; Or it is a half-battery, whose battery structure includes a positive electrode shell, a positive electrode material, an electrolyte, a separator, an electrolyte, a negative electrode material, a gasket, a spring sheet and a negative electrode shell; The positive electrode material is Ti foil; The negative electrode material is a zinc metal foil with an artificial interface layer, and the artificial interface layer includes 1,3,5,9-tetrathienylpyrene and a binder; The electrolyte is a ZnSO4 aqueous solution.

8. The aqueous zinc ion battery according to claim 7, characterized in that: The positive electrode shell is a stainless steel button battery shell CR2032 model, the gasket and spring sheet are stainless steel sheets, the negative electrode shell is a stainless steel button battery shell CR2032 model, the diaphragm is Whatman GF / F glass fiber filter paper with a diameter of 1.6 cm, and the concentration of the electrolyte is 2 mol·L -1 , the thickness of the Ti foil is 0.02 mm.

9. A method for preparing an aqueous zinc ion battery according to claim 7, characterized in that: The following steps are involved: 1) Treatment of positive electrode shell, negative electrode shell, gasket and spring sheet: The positive electrode shell, the negative electrode shell, the gasket, and the spring sheet are ultrasonically cleaned using deionized water and anhydrous ethanol respectively; 2) Preparation and processing of negative electrode sheets: The zinc metal foil is polished with sandpaper to remove zinc oxide on the surface, and then the polished zinc metal foil is made into an electrode sheet with a punch, and the electrode sheet is placed in a coating machine, and a mixed solution including 1,3,5,9-tetrathienylpyrene and a binder is spin-coated, and then vacuum drying is performed; 3) Assembly of symmetrical batteries: Put the spring sheet, gasket, and negative electrode sheet in the negative electrode shell respectively, drip the electrolyte, put the diaphragm, and then drip the electrolyte to make the diaphragm completely soaked, put the positive electrode sheet in full alignment with the negative electrode sheet, then buckle the positive electrode shell, put it in a plastic ziplock bag and transfer it to the hydraulic battery packaging machine for packaging; Or 4) Assembly of half-cell: Put the spring sheet, gasket and negative electrode sheet into the negative electrode shell respectively, drip the electrolyte, put in the diaphragm, and then drip the electrolyte to make the diaphragm completely soaked, put the positive electrode sheet Ti foil in full alignment with the negative electrode sheet, then buckle the positive electrode shell, put it into a plastic ziplock bag and transfer it to the hydraulic battery packaging machine for packaging.

10. The preparation method according to claim 9, characterized in that: The mixed solution comprising 1,3,5,9-tetrathienylpyrene and a binder in step 2) is specifically a solution in which the solute is 1,3,5,9-tetrathienylpyrene and the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone.